The effects of melatonin on oxidative stress and prevention of primordial follicle loss via activation of mTOR pathway in the rat ovary - Behram Kandemir, Y.; Aydin, C.; Gorgisen, G. (Cellular and Molecular Biology, 2017)
Mammalian Target of Rapamycin (mTOR) signaling pathway has important roles in the regulation of puberty onset, gonadotropin secretion, follicular development and ovulation. Melatonin (N-acetyl-5-methoxytryptamine) is a lipophilic hormone has multiple functions in regulating the fertility. Recent studies have shown that melatonin affected the number or maturation of follicles in the ovary. The aim of this study was to investigate the effects of melatonin on mTOR expression and quantity of follicle in rat ovary. In the present study, a total of 45 female rats were randomly divided into three groups. Group 1; Control (C), Group 2: Vehicle (V) and Group 3; Melatonin (M). Melatonin was administered intraperitoneally at a dose of 50 mg/kg/day for 30 days in Melatonin group. The effects of Melatonin on the expression of mTOR and downstream components  were determined by Western Blot and Reverse Transcriptase PCR analysis. Upon Western Blot and RT-PCR evaluations, we detected higher expression and activation of mTOR, P70S6K, PKCalpha, PCNA and higher numbers of primordial  follicles in melatonin group compared with V and C group. In addition to this results, melatonin decreased oxidative stress markers, such as MDA, on the contrary, levels of antioxidative markers, such as CAT and GPx, were increased by melatonin in rat ovary. This study indicated that melatonin may have a significant protective effect on primordial follicles and increase the expression of mTOR and downstream components in rat ovary. Melatonin treatment may have a beneficial effect on fertility.